Continuous fiber reinforced polyaryletherketone composite material with low porosity and high interfacial strength and preparation method thereof

By using bisphenol AF type polyaryletherketone with imide-containing side groups as an interface wetting agent, the interface bonding performance between fiber and polyaryletherketone material is improved, and the problem of weak bonding force between polyaryletherketone resin and fiber is solved, and a continuous fiber-reinforced polyaryletherketone composite material with low porosity and high interface strength is achieved.

CN119752148AInactive Publication Date: 2025-04-04江苏君华特种高分子材料股份有限公司 +1

Patent Information

Application Number
CN202510019653.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-04
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The high solubility and high viscosity of polyaryletherketone resin lead to weak bonding power with fibers, resulting in high porosity and tendency to crack in the composite material, affecting the stability of the material's performance.

Method used

Bisphenol AF type polyaryletherketone (PI-PAEK) containing imide-containing pendant groups is used as the interface wetting agent for continuous fibers. The interface bonding performance between the fiber and the polyaryletherketone material is improved through the steps of high-temperature deslurry, plasma treatment and resizing.

Benefits of technology

The porosity of the composite material is significantly reduced, the interfacial strength and mechanical properties are improved, the porosity is less than 1%, the tensile strength is more than 900MPa, and the interlayer shear strength is more than 120MPa.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005230947750000021
    Figure BDA0005230947750000021
  • Figure BDA0005230947750000041
    Figure BDA0005230947750000041
  • Figure BDA0005230947750000051
    Figure BDA0005230947750000051
Patent Text Reader

Abstract

The invention relates to the technical field of high polymer material processing, in particular to a low-porosity and high-interfacial-strength continuous-fiber-reinforced polyaryletherketone composite material and a preparation method thereof, and the preparation method is characterized in that continuous fibers are subjected to high-temperature desizing, plasma treatment, re-sizing with an interface impregnating compound and compounding with polyaryletherketone resin to prepare the low-porosity and high-interfacial-strength continuous-fiber-reinforced polyaryletherketone composite material. The continuous fiber reinforced polyaryletherketone composite material is obtained; specifically, the interface impregnating compound is bisphenol AF type polyaryletherketone containing imide side groups, so that the interface bonding performance between the continuous fibers and the polyaryletherketone material can be effectively improved, the prepared composite material has excellent mechanical properties, and the porosity is lower than 1%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer material processing, and in particular to a low-porosity, high-interface-strength continuous-fiber-reinforced polyaryletherketone composite material and a preparation method thereof. Background Art

[0002] The polyaryletherketone (PAEK) series of materials, due to their specific structural units on the molecular chain, are widely recognized as high-temperature resistant thermoplastic special engineering plastics with excellent comprehensive performance. Representative varieties include PEEK, PEKK, PEK and PEKEKK.

[0003] Carbon fiber composite materials are characterized by continuous fibers, and their mechanical properties are deeply affected by the weaving process. Common weaving techniques include unidirectional weaving, biaxial plain weaving, twill weaving, three-dimensional weaving, circular weaving and warp weaving.

[0004] Compared with traditional thermosetting composite materials, continuous fiber reinforced polyaryletherketone materials have many advantages: low density, light weight; support for room temperature storage, short molding cycle, no post-processing steps, can be hot-melt butt joint, low assembly cost and high efficiency; good toughness and damage tolerance; excellent resistance to moisture and heat; strong chemical stability, significant resistance to corrosion and medium erosion; good flame retardancy, low smoke and non-toxicity, low volatile matter; recyclable, high resource utilization. These characteristics make them very suitable for fields with complex shapes or high requirements for material properties.

[0005] However, the high solubility difficulty of polyaryletherketone resin makes it difficult to prepare continuous fiber reinforced polyaryletherketone unidirectional tape and composite materials through traditional solution impregnation and other processes. In addition, the high viscosity and surface inertness of polyaryletherketone melt lead to weak bonding with fibers, which causes high porosity and cracking tendency of composite materials, thus affecting the stability of material properties. Summary of the invention

[0006] In order to solve the above technical problems, a low porosity, high interface strength continuous fiber reinforced polyaryletherketone composite material and a preparation method thereof are provided. The present invention adopts bisphenol AF type polyaryletherketone (PI-PAEK) containing imide side groups as the interface impregnating agent of the continuous fiber, which can effectively improve the interface bonding performance between the continuous fiber and the polyaryletherketone material. The prepared continuous fiber reinforced polyaryletherketone composite material has excellent mechanical properties and a porosity of less than 1%.

[0007] In order to achieve the above objectives, the present invention is implemented by the following technical solutions:

[0008] A low-porosity, high-interface-strength continuous-fiber-reinforced polyaryletherketone composite material, comprising, by weight percentage, 100% of the material composition: more than 30% by weight of the interface-wetting continuous fiber, and more than 35% by weight of the polyaryletherketone resin;

[0009] The interface impregnated continuous fibers contain at least 0.5 wt% of the interface impregnated continuous fibers;

[0010] The interfacial wetting agent is a bisphenol AF type polyaryletherketone containing an imide side group, and has the following chemical structure:

[0011]

[0012] Where n represents the degree of polymerization, the number average molecular weight is 10,000 to 30,000 g / mol, the weight average molecular weight is 30,000 to 60,000 g / mol, and the PDI is in the range of 1-3.

[0013] Furthermore, the material composition of 100% by weight includes: 35%-50% of the interface impregnated continuous fiber, 50%-65% of the polyaryletherketone resin;

[0014] The interface wetting agent in the interface wetting continuous fiber accounts for 1wt%-15wt%.

[0015] Furthermore, the interface impregnated continuous fiber is a product of a continuous fiber that is de-sized, treated with plasma, and then re-sized with an interface impregnating agent.

[0016] Furthermore, the continuous fiber is selected from one or more of carbon fiber cloth, aramid fiber cloth, PBO fiber cloth, glass fiber cloth, and basalt fiber cloth; the polyaryletherketone is selected from one or more of PEEK, PEKK, PEK, and PEKEKK.

[0017] Another aspect of the present invention provides a method for preparing a low-porosity, high-interface-strength continuous-fiber-reinforced polyaryletherketone composite material, comprising the following steps:

[0018] S1, desizing the continuous fiber at a high temperature of at least 250° C., treating it with plasma, and then resizing it with an interface wetting agent to obtain an interface-wetted continuous fiber;

[0019] S2, making the interface impregnated continuous fiber and polyaryletherketone resin form a composite, that is, obtaining a continuous fiber reinforced polyaryletherketone composite material.

[0020] Furthermore, the operation of re-sizing with the interface wetting agent is: dissolving the interface wetting agent in an organic solvent to form an interface wetting agent solution with a mass percentage greater than 10%, and then immersing the continuous fiber treated in the previous step into the interface wetting agent solution, drying it in the range of 200-240°C for 2-8h, and repeating or not repeating the immersion-drying operation to the desired interface wetting agent content ratio.

[0021] Furthermore, the mass percentage of the interface wetting agent solution is 15%-60%; the organic solvent is selected from one or more of tetrahydrofuran (THF), chloroform (CHCl3), N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), N-methylpyrrolidone (NMP), and dimethyl sulfoxide (DMSO).

[0022] Furthermore, the plasma treatment is carried out under normal pressure, the treatment atmosphere is one or more of air, oxygen, nitrogen, and argon, and the power of the plasma treatment is 50 W / cm 3 -1000W / cm 3 , processing time is 10s-150s;

[0023] The high-temperature desizing temperature is in the range of 250-500° C., and the desizing time is at least 1 hour.

[0024] Furthermore, the composite is formed by alternately stacking polyaryletherketone resin films and continuous fibers and then performing compression molding, wherein the thickness of the polyaryletherketone resin films is in the range of 0.05 mm to 0.5 mm.

[0025] Furthermore, the parameters of the compression molding are: heating to 370-420°C at a heating rate of 10-20°C / min, continuously pressurizing to 0.5-5MPa during the heating process, processing time of 6-24h, and then cooling to room temperature at a cooling rate of 5-15°C / min.

[0026] Beneficial technical effects:

[0027] The present invention utilizes the good room temperature solubility of bisphenol AF type polyaryletherketone (PI-PAEK) containing imide side groups to re-size the continuous fiber after high-temperature desizing, thereby overcoming the problem that the traditional polyaryletherketone resin is insoluble; the present invention uses bisphenol AF type polyaryletherketone (PI-PAEK) containing imide side groups as the continuous fiber interface impregnant, utilizes the activity of the imide side groups, and after the fiber surface is treated with plasma, active groups such as -COOH, -C-NH2, and -OH are generated on the fiber surface. The active groups react chemically with the imide side groups in the bisphenol AF type polyaryletherketone (PI-PAEK) resin containing imide side groups. At the same time, the main chain of the interface impregnant is similar to the structure of the matrix resin polyaryletherketone of the composite material, resulting in good compatibility, and a strong linking bridge is established between the continuous fiber and the polyaryletherketone resin, effectively improving the interface bonding performance between the polyaryletherketone resin and the continuous fiber, and obtaining a continuous fiber reinforced polyaryletherketone composite material with excellent performance, and the porosity of the composite material is reduced to less than 1%;

[0028] The composite material of the invention has a tensile strength of more than 900 MPa and an interlaminar shear strength of more than 120 MPa, and has good overall performance, providing a new product for polyaryletherketone raw materials used in the fields of aerospace, military industry, medical treatment, automobiles, machinery, electronics, etc. DETAILED DESCRIPTION

[0029] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present invention and its application or use. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] Unless otherwise specifically stated, the numerical value set forth in these embodiments does not limit the scope of the present invention. The technology and method known to those of ordinary skill in the relevant art may not be discussed in detail, but in appropriate cases, the technology and method should be considered as a part of the specification. In all examples shown and discussed here, any specific value should be interpreted as being merely exemplary, rather than as a limitation. Therefore, other examples of exemplary embodiments may have different values.

[0031] The experimental methods in the following examples without specifying specific conditions are usually measured in accordance with national standards; if there is no corresponding national standard, the method is carried out in accordance with the general standard requirements or general methods.

[0032] The polyaryletherketone resin film used below takes PEEK film as an example. The PEEK film is provided by Jiangsu Junhua Special Polymer Materials Co., Ltd. The melt index range of the PEEK resin used to produce the PEEK film is 8-10g / 10min (400°C, 2.16Kg), and the film thickness is 0.05-0.2mm.

[0033] The preparation method of the bisphenol AF type polyaryletherketone (PI-PAEK) containing imide side groups used below can be found in the Chinese patent application number 202411516988.7 of Shandong Junhao High Performance Polymer Co., Ltd., which describes the preparation method of the polymer in detail in Example 1. Specifically, it is prepared by condensation polymerization of bisphenol AF containing two imide groups and 4,4'-difluorobenzophenone.

[0034] The continuous fiber used below is a continuous carbon fiber cloth, provided by Jiangsu Junhua Special Polymer Materials Co., Ltd., plain weave, 200g / m 2 .

[0035] Preparation Example 1

[0036] According to the method of Example 1 in the Chinese patent application number 202411516988.7 of Shandong Junhao High Performance Polymer Co., Ltd., bisphenol AF containing two imide groups is first synthesized, and then bisphenol AF type polyaryletherketone (PI-PAEK) containing imide side groups is produced;

[0037] Specific preparation process: (1) Synthesis of bisphenol AF containing two imide groups (i.e. monomer a)

[0038]

[0039] In a 1000mL three-necked flask equipped with a reflux condenser, a nitrogen inlet and outlet, and an electric stirrer, 322gDMF, 73.25g (0.2mol) 2,2-bis (3-amino-4-hydroxyphenyl) hexafluoropropane, and 65.17g (0.44mol) phthalic anhydride were added in sequence. Stir and dissolve at room temperature and react for 6h. Then add 31mL acetic anhydride and continue stirring for 1h. Then add 31mL triethylamine and continue stirring for 1h. After the reactants are cooled to room temperature, pour them into a poor solvent such as pure water, and the resulting precipitate is repeatedly washed with pure water. After the product is dried, it is recrystallized with an ethyl acetate / toluene mixture. After filtering and drying the crystallized product, bisphenol AF (i.e., monomer a) containing two imide groups is obtained. The yield is 73%.

[0040] Monomer a 1H NMR: δH(DMSO-d6,400MHz)10.45(s,2H,OH),7.85-7.95(m,8H,Ar-H),7.40(s,2H,Ar-H),7.20-7.25(d,2H,Ar-H),7.05-7.10(d,2H,Ar-H).

[0041] FTIR of bisphenol AF containing imide (cm -1 ):3390(-OH),1785(imide,C=O),1716(imide,C=O),1387(CN),1253(CF3).

[0042] DSC: Tm of monomer a is 192-194°C.

[0043] (2) Synthesis of bisphenol AF polyaryletherketone (PI-PAEK) containing imide side groups

[0044]

[0045] In a 1000mL three-necked flask equipped with a mechanical stirrer, nitrogen inlet and outlet, water separator and reflux condenser, add 62.65g (0.1mol) of diphenol monomer a (bisphenol AF containing imide in step 1), 21.82g (0.1mol) of 4,4'-difluorobenzophenone, 18.0g (0.13mol) of anhydrous K2CO3, 235g of DMF and 25mL of toluene. Under N2 atmosphere, stir at 60°C until the solid material is completely dissolved. After stirring and heating at 140°C for 2h, the generated water azeotropes with toluene, and the azeotropes are removed through the water separator. Then, the polymerization reaction was continued at 160°C with stirring for 7 hours to obtain a viscous mixed liquid; the viscous mixed liquid was poured into a mixed solution of 600 mL of ethanol and water (volume ratio of 1:1) to precipitate a polymer; it was soaked in a hot ethanol-water solution (volume ratio of ethanol to water of 1:2, temperature of 80°C) for 30 minutes, repeated three times, and after filtering and drying, bisphenol AF type polyaryletherketone (PI-PAEK) containing imide side groups was obtained.

[0046] Example 1

[0047] A method for preparing a low-porosity, high-interface-strength continuous-fiber-reinforced polyaryletherketone composite material comprises the following steps:

[0048] S1. The continuous carbon fiber cloth is placed in an environment of 320°C for high temperature desizing for 3 hours, and then subjected to normal pressure plasma treatment. The treatment atmosphere is air and the treatment power is 100W / cm 3 , the treatment time is 50s, and the treated continuous carbon fiber cloth is obtained;

[0049] The continuous carbon fiber cloth treated in the previous step was re-sized using the PI-PAEK prepared in Preparation Example 1 as an interface impregnating agent. Specifically, 10 kg of the continuous carbon fiber cloth treated in the previous step was immersed in a PI-PAEK solution (solvent: DMAc) having a mass fraction of 40% for a period of time, and then dried at 210° C. for 5 h to obtain 11.1 kg of interface impregnated continuous carbon fiber cloth.

[0050] The weight of the fiber after plasma treatment and the weight of the fiber after re-sizing and drying are weighed respectively, and the weight difference between the two is the sizing amount of the interface impregnant; the required sizing amount is controlled by the immersion time of the fiber cloth in the PI-PAEK solution and the concentration of the F-PAEK solution;

[0051] The interface impregnating agent PI-PAEK in the interface impregnated continuous carbon fiber cloth described in this case accounts for about 9.9%;

[0052] S2. Compounding the interface-impregnated continuous fiber with polyaryletherketone resin: 10 PEEK films (thickness 0.15 mm) and 9 interface-impregnated continuous carbon fiber cloths are alternately stacked in a molding die. During molding, the temperature is increased to 385°C at a heating rate of 15°C / min, and the pressure is continuously increased to 1.5 MPa during the heating process. The processing time is 12 hours, and then the temperature is cooled to room temperature at a cooling rate of 10°C / min to obtain a low-porosity, high-interface-strength continuous fiber-reinforced polyaryletherketone composite material. According to the material composition of 100% by mass, the interface-impregnated continuous carbon fiber cloth accounts for 50% and the PEEK resin accounts for 50%.

[0053] Example 2

[0054] A method for preparing a low-porosity, high-interface-strength continuous-fiber-reinforced polyaryletherketone composite material comprises the following steps:

[0055] S1. The continuous carbon fiber cloth is placed in an environment of 350°C for high temperature desizing for 2 hours, and then subjected to normal pressure plasma treatment. The treatment atmosphere is air and the treatment power is 200W / cm 3 , the treatment time is 100s, and the treated continuous carbon fiber cloth is obtained;

[0056] The continuous carbon fiber cloth treated in the previous step was re-sized using the PI-PAEK prepared in Preparation Example 1 as an interface impregnating agent. Specifically, 10 kg of the continuous carbon fiber cloth treated in the previous step was immersed in a PI-PAEK solution (solvent: DMF) with a mass fraction of 55% for a period of time, and then dried at 230° C. for 4 hours to obtain 11.5 kg of interface impregnated continuous carbon fiber cloth;

[0057] The weight of the fiber after plasma treatment and the weight of the fiber after re-sizing and drying are weighed respectively, and the weight difference between the two is the sizing amount of the interface impregnant; the required sizing amount is controlled by the immersion time of the fiber cloth in the PI-PAEK solution and the concentration of the F-PAEK solution;

[0058] The interface impregnating agent PI-PAEK in the interface impregnated continuous carbon fiber cloth described in this case accounts for about 13.0%;

[0059] S2. Compounding the interface-impregnated continuous fiber with polyaryletherketone resin: 10 PEEK films (thickness 0.15 mm) and 9 interface-impregnated continuous carbon fiber cloths are alternately stacked in a molding die. During molding, the temperature is increased to 385°C at a heating rate of 15°C / min. The pressure is continuously increased to 3MPa during the heating process. The processing time is 6 hours. The temperature is then cooled to room temperature at a cooling rate of 10°C / min. Thus, a low-porosity, high-interface-strength continuous fiber-reinforced polyaryletherketone composite material is obtained. According to the material composition of 100% by mass, the interface-impregnated continuous carbon fiber cloth accounts for 51% and the PEEK resin accounts for 49%.

[0060] Example 3

[0061] A method for preparing a low-porosity, high-interface-strength continuous-fiber-reinforced polyaryletherketone composite material comprises the following steps:

[0062] S1. The continuous carbon fiber cloth is placed in an environment of 400°C for high temperature desizing for 3 hours, and then subjected to normal pressure plasma treatment. The treatment atmosphere is air and the treatment power is 300W / cm 3 , the treatment time is 150s, and the treated continuous carbon fiber cloth is obtained;

[0063] The continuous carbon fiber cloth treated in the previous step was re-sized using the PI-PAEK prepared in Preparation Example 1 as an interface impregnating agent. Specifically, 10 kg of the continuous carbon fiber cloth treated in the previous step was immersed in a PI-PAEK solution (solvent: DMF) with a mass fraction of 30% for a period of time, and then dried at 240° C. for 3 h to obtain 10.65 kg of interface impregnated continuous carbon fiber cloth;

[0064] The weight of the fiber after plasma treatment and the weight of the fiber after re-sizing and drying are weighed respectively, and the weight difference between the two is the sizing amount of the interface impregnant; the required sizing amount is controlled by the immersion time of the fiber cloth in the PI-PAEK solution and the concentration of the F-PAEK solution;

[0065] The interface impregnating agent PI-PAEK in the interface impregnated continuous carbon fiber cloth described in this case accounts for about 6.1%;

[0066] S2. Compounding the interface impregnated continuous fiber with polyaryletherketone resin: 10 PEEK films (thickness 0.15 mm) and 9 interface impregnated continuous carbon fiber cloths are alternately stacked in a molding die. During molding, the temperature is increased to 385°C at a heating rate of 15°C / min, and the pressure is continuously increased to 2 MPa during the heating process. The processing time is 8 hours, and then the temperature is cooled to room temperature at a cooling rate of 10°C / min to obtain a low porosity and high interface strength continuous fiber reinforced polyaryletherketone composite material. According to the material composition of 100% by mass, the interface impregnated continuous carbon fiber cloth accounts for 49% and the PEEK resin accounts for 51%.

[0067] Comparative Example 1

[0068] The composite material preparation process of this case is the same as that of Example 1, except that the continuous carbon fiber cloth is not subjected to high-temperature desizing, plasma treatment, and resizing, and the continuous carbon fiber cloth without any treatment and the PEEK film are directly used for S4 compression molding.

[0069] Comparative Example 2

[0070] The composite material preparation process of this case is the same as that of Example 1, except that the continuous carbon fiber cloth is not subjected to plasma treatment and re-sizing, and the continuous carbon fiber cloth that has only been desized at high temperature and the PEEK film are used for compression molding.

[0071] Comparative Example 3

[0072] The composite material preparation process of this case is the same as that of Example 1, except that the continuous carbon fiber cloth is not re-sized, and the continuous carbon fiber cloth and PEEK film that have been desized at high temperature and plasma treated are used for compression molding.

[0073] Comparative Example 4

[0074] The preparation process of the composite material in this case is the same as that in Example 1, except that the interface wetting agent for re-sizing is sulfonated polyetheretherketone S-PEEK with a sulfonation degree of 36%, provided by Shandong Junhao High Performance Polymer Co., Ltd., and prepared by conventional concentrated sulfuric acid sulfonation method.

[0075] Comparative Example 5

[0076] The preparation process of the composite material in this case is the same as that in Example 1, except that the interface wetting agent for re-sizing is hexafluorobisphenol A type polyaryletherketone PAEK-AF, prepared with reference to Jiang Zhenyu et al., Synthesis and Properties of Polyaryletherketone and Polyarylethersulfone Containing Hexafluoroisopropane Structure [J]. Journal of East China University of Science and Technology (Natural Science Edition), 2007, Vol. 33, No. 3, P345-349, and the chemical structure is as follows:

[0077]

[0078] Test Case

[0079] The above embodiments and comparative examples were subjected to performance tests, and the test results are shown in Table 1.

[0080] Table 1 Performance of Examples and Comparative Examples

[0081] Porosity (%) Tensile strength MPa Interlaminar shear strength MPa Example 1 0.82 948 124 Comparative Example 1 2.96 609 65 Comparative Example 2 2.84 683 79 Comparative Example 3 2.78 756 92 Comparative Example 4 1.65 886 105 Comparative Example 5 2.05 780 92 Example 2 0.76 1023 128 Example 3 0.90 916 121 Test Standards GB / T 3365 ASTM D3039 ASTM D2344

[0082] As can be seen from Table 1, the composite material of Comparative Example 1 did not perform any treatment on the carbon fiber cloth, and its porosity was relatively high, close to 3%, the tensile strength was only 609MPa, and the interlaminar shear strength was only 65MPa. This is because the epoxy sizing agent originally existed on the surface of the carbon fiber cloth, which was easily volatilized during the subsequent compression molding process, resulting in the deterioration of the bonding performance and mechanical properties of PEEK and carbon fiber cloth. In Comparative Example 2, the tensile strength and interlaminar shear strength of the carbon fiber cloth that only used high-temperature desizing increased slightly, especially the decrease in porosity was not obvious. In Comparative Example 3, the porosity of the carbon fiber cloth treated with high-temperature desizing and plasma was further reduced, but the decrease was not obvious, and the tensile strength and interlaminar shear strength were improved. Compared with the embodiment, the interface wetting agent was replaced in Comparative Examples 4 and 5. Since sulfonated PEEK is soluble in organic solvents and rich in sulfonic acid groups, it can react with the groups generated by plasma, thereby increasing the adhesion to the matrix resin, significantly improving the tensile strength and interlaminar shear strength, and reducing the porosity to 1.65%. However, since hexafluorobisphenol A type polyaryletherketone has no active groups and does not react accordingly with the groups generated by plasma, its improvement in the performance of the composite material is not as good as sulfonated PEEK.

[0083] The composite material of the present invention adopts carbon fiber cloth which has been subjected to high temperature desizing, plasma treatment and resizing in sequence. After being compounded with matrix resin, the composite material has a porosity of less than 1%, a tensile strength of more than 900 MPa and an interlaminar shear strength of more than 120 MPa.

[0084] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. Low porosity, high interface strength continuous fiber reinforced polyaryletherketone composite material, characterized in that: The material composition of 100% by weight includes: interface impregnated continuous fibers accounting for more than 30wt% and polyaryletherketone resin accounting for more than 35%; The interface impregnated continuous fibers contain at least 0.5 wt% of the interface impregnated continuous fibers; The interfacial wetting agent is a bisphenol AF type polyaryletherketone containing an imide side group, and has the following chemical structure: Where n represents the degree of polymerization, the number average molecular weight is 10,000 to 30,000 g / mol, the weight average molecular weight is 30,000 to 60,000 g / mol, and the PDI is in the range of 1-3.

2. The low porosity and high interface strength continuous fiber reinforced polyaryletherketone composite material according to claim 1, characterized in that: According to the weight percentage, 100% of the material composition includes: 35%-50% of the interface impregnated continuous fiber, 50%-65% of the polyaryletherketone resin; The interface wetting agent in the interface wetting continuous fiber accounts for 1wt%-15wt%.

3. The low porosity and high interface strength continuous fiber reinforced polyaryletherketone composite material according to claim 2, characterized in that: The interface impregnated continuous fiber is a product obtained by removing the sizing agent from the continuous fiber, treating it with plasma, and then re-sizing it with an interface impregnating agent.

4. The low porosity and high interface strength continuous fiber reinforced polyaryletherketone composite material according to claim 3, characterized in that: The continuous fiber is selected from one or more of carbon fiber cloth, aramid fiber cloth, PBO fiber cloth, glass fiber cloth, and basalt fiber cloth; the polyaryletherketone is selected from one or more of PEEK, PEKK, PEK, and PEKEKK.

5. The method for preparing a low-porosity, high-interface-strength continuous-fiber-reinforced polyaryletherketone composite material according to any one of claims 1 to 4, characterized in that: The steps include: S1, desizing the continuous fiber at a high temperature of at least 250° C., treating it with plasma, and then resizing it with an interface wetting agent to obtain an interface-wetted continuous fiber; S2, making the interface impregnated continuous fiber and polyaryletherketone resin form a composite, that is, obtaining a continuous fiber reinforced polyaryletherketone composite material.

6. The method for preparing a low-porosity, high-interface-strength continuous-fiber-reinforced polyaryletherketone composite material according to claim 5, characterized in that: The operation of re-sizing with the interface wetting agent is: dissolving the interface wetting agent in an organic solvent to form an interface wetting agent solution with a mass percentage greater than 10%, then immersing the continuous fiber treated in the previous step into the interface wetting agent solution, drying at 200-240° C. for 2-8 hours, and repeating or not repeating the immersion-drying operation until the desired interface wetting agent content is reached.

7. The method for preparing a low-porosity, high-interface-strength continuous-fiber-reinforced polyaryletherketone composite material according to claim 6, characterized in that: The mass percentage of the interface wetting agent solution is 15%-60%; the organic solvent is selected from one or more of tetrahydrofuran, chloroform, N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, and dimethyl sulfoxide.

8. The method for preparing a low-porosity, high-interface-strength continuous-fiber-reinforced polyaryletherketone composite material according to claim 6, characterized in that: The plasma treatment is carried out under normal pressure, the treatment atmosphere is one or more of air, oxygen, nitrogen, and argon, and the power of the plasma treatment is 50 W / cm 3 -1000W / cm 3 , processing time is 10s-150s; The high-temperature desizing temperature is in the range of 250-500° C., and the desizing time is at least 1 hour.

9. The method for preparing a low-porosity, high-interface-strength continuous-fiber-reinforced polyaryletherketone composite material according to claim 6, characterized in that: The composite method is to use polyaryletherketone resin film and continuous fiber to alternately stack and arrange them and then perform compression molding.

10. The method for preparing a low-porosity, high-interface-strength continuous-fiber-reinforced polyaryletherketone composite material according to claim 9, characterized in that: The parameters of the compression molding are: heating to 370-420°C at a heating rate of 10-20°C / min, continuously pressurizing to 0.5-5MPa during the heating process, processing time of 6-24h, and then cooling to room temperature at a cooling rate of 5-15°C / min.

Citation Information

Patent Citations

  • Polyaryletherketone resin containing imide side group and preparation method of polyaryletherketone resin

    CN119390967A

  • Continuous fiber-reinforced polyaryletherketone composite material and preparation method thereof

    CN110387119A

  • Continuous fiber reinforced polyaryletherketone composite material and preparation method thereof

    CN110499012A

  • High-strength and high-toughness modified PEEK composite material and preparation method thereof

    CN117700922A

  • Continuous fiber reinforced polyether-ether-ketone unidirectional belt and preparation method thereof

    CN118027599A

Cited By

  • Continuous fiber reinforced sulfonated polyetheretherketone water lubricating material and preparation method thereof

    CN121403794A